Pengembangan Bahan Ajar Terampil Menulis Berbasis Project Based Learning Mahasiswa PBSI Universitas Islam Malang - Itznaniyah Umie Murniatie; Hasan Busri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
One of the essential competencies provided to students is writing. In fact, there are still many students who are not skilled at writing. This research aims to find out the process and results of the trial Development of Skilled Teaching Materials Writing Based Project-Based Learning PBSI Malang Islamic University Students. The method utilized is the research development research and development (R&D) addie model. Data collection techniques use questionnaires and tests. Techniques analyze data, used T-test to test the effectiveness of the product. The results of this study found there was an average difference between pre-test results and post-tests, which means the use of Skilled Writing Based Teaching Materials Project-Based Learning proved effective. Salah satu kompetensi yang penting dibekali kepada mahasiswa adalah menulis. Pada kenyataannya, masih banyak mahasiswa yang belum terampil menulis. Penelitian ini bertujuan mengetahui proses dan hasil uji coba pengembangan bahan ajar terampil menulis berbasis project based learning mahasiswa PBSI Unisma. Metode yang dimanfaatkan adalah penelitian pengembangan research and development (R&D) model ADDIE. Teknik pengumpulan data menggunakan angket dan tes. Teknik menganalisis data menggunakan uji T untuk menguji efektivitas produk. Hasil penilitian ini ditemukan terdapat perbedaan rata-rata antara hasil pre test dengan post test yang artinya penggunaan bahan ajar terampil menulis berbasis project based learning terbukti efektif.